Damar Kurung Melintas Waktu: Preserving Local Culture in the Age of Digital Society - Ika Anggun Camelia; Djuli Djatiprambudi; Martadi; Fera Ratyaningrum (Sanggitarupa, 2026)
Cultural conservation is an essential component in efforts to preserve cultural values because it is closely related to strengthening, preserving the environment, and sustainable learning and education. This research aims to identify a form of conservation as well as a supporting factor for the success of local cultural conservation in the digital society era. The research method used is descriptive qualitative through a case study  of the “Damar Kurung Melintas Waktu" Exhibition in Gresik, East Java. The findings indicate forms of cultural conservation that have been carried out by the Gresik Community, including the digitization of Damar Kurung, diversification of forms, and the development of Damar Kurung as a source of inspiration. “Damar Kurung Melintas Waktu" Exhibition  was attended by 22 artists and there were 7 activities consisting of 4 discussion forums and 3 workshops. The factors that affect cultural conservation include the role of the environment and community, government support, cultural digitalization, innovation and creative adaptation, education based on local wisdom, and the role of social media in promoting local culture. The digital society can embrace local culture as long as it is preserved in ways that are relevant to contemporary social practices.